Language learning strategies in independent language learning: an overview. - White CJ (Multilingual Matters, 2008)
The notions of independence, autonomy, and control in learning experiences have come to play an increasingly important role in language education. A number of principles underpin independent language learning – optimising or extending learner choice, focusing on the needs of individual learners, not the interests of a teacher or an institution, and the diffusion of decision-making to learners. Independent language learning (ILL) reflects a move towards more learner-centred approaches viewing learners as individuals with needs and rights, who can develop and exercise responsibility for their learning. An important outgrowth of this perspective has been the range of means developed to raise learners’ awareness and knowledge of themselves, their learning needs and preferences, their beliefs and motivation and the strategies they use to develop target language (TL) competence. In this chapter I begin with an overview of the concept of independent language learning, and of the particular contribution of language learning strategies to this domain. I argue that a fundamental challenge of independent language learning is for learners to develop the ability to engage with, interact with, and derive benefit from learning environments which are not directly mediated by a teacher. Drawing on learner conceptualisations of distance language learning I argue that learners develop this ability largely by constructing a personally meaningful interface with the learning context, and that strategies play a key role in this regard. In the latter half of the chapter I focus on a series of landmark studies, identifying how they illuminate important aspects of independent language learning, extend our understanding of strategies and strategy development, and provide insights into how students use strategies within independent learning contexts. The following three sections provide historical and theoretical background, while the two main sections in the remainder of the chapter provide a state of the art overview of language learning strategies in ILL.
Keywords: Fields of Research::420000 Language and Culture::420100 Language Studies